Histopathological and Molecular Study of Pacific Oyster Tissues Provides Insights into V. aestuarianus Infection Related to Oyster Mortality - Daniela Mandas; Fulvio Salati; Marta Polinas; Marina Antonella Sanna; Rosanna Zobba; Giovanni Pietro Burrai; Alberto Alberti; Elisabetta Antuofermo (Pathogens, 2020)
Consumer preference for healthy and sustainable food products has been steadily increasing in recent years. Bivalve mollusks satisfy these characteristics and have captured ever-increasing market shares. However, the expansion of molluscan culture in worldwide and global trade have favored the spread of pathogens around the world. Combined with environmental changes and intensive production systems this has contributed to the occurrence of mass mortality episodes, thus posing a threat to the production of different species, including the Pacific oyster Crassotrea gigas. In the San Teodoro lagoon, one of the most devoted lagoons to extensive Pacific oyster aquaculture in Sardinia, a mortality outbreak was observed with an estimated 80% final loss of animal production. A study combining cultural, biomolecular and histopathological methods was conducted: (1) to investigate the presence of different Vibrio species and OsHV-1 in selected oyster tissues (digestive gland, gills, and mantle); (2) to quantify Vibrio aestuarianus and to evaluate the severity of hemocyte infiltration in infected tissues; (3) to produce post-amplification data and evaluating ToxR gene as a target for phylogenetic analyses. Results provide new insights into V. aestuarianus infection related to oyster mortality outbreaks and pave the way to the development of tools for oyster management.